A Review of the Toxic effects and Methods of Reducing the Pesticide of Organophosphate Malathion in Food - Mehran Sayadi; Mohammad Kiani; Ameneh Nematollahi; Roghayeh Nejati; Hashymihe Kabbidoraghi (Fasa University of Medical Sciences, 2020)
Nowadays, food safety and security is one of the main issues of human life concerns. Parallel to this, food health also becomes significant for agricultural product consumers. Although organophosphate pesticides such as malathion can have adverse effects on consumer health, they are widely used in food production to increase food security. Results show that besides pesticides benefits, there are some problems such as reduced biodiversity, reduced nitrogen fixation and destruction of fauna residential place specially birds and endangered species. Some of the used pesticides have side effects such as increased salivation, nasal and eye discharge, bronchoconstriction, meiosis, gastrointestinal cramps, high blood pressure and various genetic disorders are left on human bodies. Due to the residues of these toxins in food products, there are many concerns for the health of consumers that use various methods such as washing, peeling and fermentation which can greatly reduce the residual pesticides in food. Although systemic toxins and penetrating toxins from fruits and vegetables do not last for a period of time after their use, they remain in agricultural products and fruits that are not removed by washing, heating, and freezing. Therefore, it is recommended that you use chemical pesticides as a last resort.